A genome-wide cross-trait analysis identifying shared genetic basis and causal relationships between Hunner-type interstitial cystitis and autoimmune diseases in East Asian populations - Lyu, Xinyi; Peng, Liao; Xu, Xueyuan; Fan, Yang; Yang, Yong; Chen, Jiawei; Liu, Mengzhu; Chen, Yuanzhuo; Zhang, Chi; Yang, Shiqin; Shen, Sihong; Zhang, Jie; et al. (Frontiers in Immunology, 2024)
PurposeEpidemiological studies have demonstrated the clinical link between Hunner interstitial cystitis (HIC) and autoimmune diseases (ADs), suggesting potential shared genetic bases for their comorbidity. We aimed to investigate the shared genetic architecture and causal relationships between HIC and ADs.MethodsWe conducted a genome-wide cross-trait study with ~170000 individuals of East Asian ancestry to investigate the shared architecture between HIC and ADs. Bidirectional Mendelian randomization (MR) was used to assess potential causal relationships and a multi-trait analysis of GWAS (MTAG) was conducted to identify their associated pleiotropic loci. Fine-mapping analysis narrowed candidate gene susceptibility loci and colocalization analysis was performed to identify shared variants at specific locus. Lastly, transcriptome-wide association (TWAS) and functional analysis were utilized to explore potential shared gene-tissue associations.ResultsThrough bidirectional MR analysis, we observed a positive causal effect of AIH(ORIVW=1.09, PIVW=1.00×10-3) and RA (ORIVW=1.47, PIVW<1.00×10-4) on HIC and a negative causal effect of UC on HIC (ORIVW=0.89, PIVW< 1.00×10-4). Furthermore, we unveiled a robust positive causal effect of HIC on T1D(ORConMix=1.05, PConMix=1.77×10-3). Cross-trait meta-analysis identified a total of 64 independent SNPs associated with HIC and ADs. Functional analysis revealed that the identified variants regulated gene expression in major tissues belonging to the autoimmune system.ConclusionsOur findings might offer insights into the shared underlying etiology of HIC and ADs.